ISLAMIC EDUCATION WITH NATIONAL INSIGHT VIEWED FROM ISLAMIC PERSPECTIVE - Syahrir, Sulthan (Jurnal Ilmiah Peuradeun, 2018)
There are three profound principles covered in this research including the Islamic view of national insight, the Islamic view of Islamic education with national insight and the implementation of Islamic education with national insight in the Republic of Indonesia. This research was intended to observe, identify and describe those issues. As the primary data were gathered by analyzing the various related literatures written by the experts of Islamic education as well as constitutional law, this research falls into the category of library research. Descriptive and analytical methods were simultaneously employed in carrying out this research.  The former was to provide a general description of the issue to be interpreted, while the latter was to scrutinize the background of the issue.  Data were then analyzed using content analysis technique.  The finding of the research reveals that the proper model of Islamic education with national insight is the one with multi ethnicity and plurality of religion and culture for the sake of the unified Republic of Indonesia, a prosperous and blessed country.